Labour market disadvantage of ethnic minority British graduates: University choice, parental background or neighbourhood? - Wouter Zwysen; Simonetta Longhi (University of Essex, Institute for Social and Economic Research (ISER), 2016)
We compare school-to-work transitions of British graduates belonging to ethnic minorities to those of white British. Six months after graduation ethnic minorities are substantially less likely to be employed than white British even after accounting for parental background, local area characteristics and detailed differences in qualifications. We show that university quality has a little impact while resources measured by parental background and the characteristics of the local area are more important for the labour market outcomes of ethnic minority graduates than for white British. Minorities lacking these resources earn less and are less likely to be employed compared to white British.
Keywords: I24; J15; R23; 330; school-to-work transitions; graduates; ethnic gaps; UK